Crustal reworking in the North China Craton at ~2.5 Ga: evidence from zircon U–Pb age, Hf isotope and whole rock geochemistry of the felsic volcano‐sedimentary rocks from the western Shandong Province. (27th February 2013) - Wang, Wei; Zhai, Mingguo; Wang, Shijin; Santosh, M.; Du, Lilin; Xie, Hangqiang; Lv, Bin; Wan, Yusheng
Abstract : The western Shandong Province (WSP) is one of the typical Neoarchaean granite–greenstone belts in the Eastern Block of the North China Craton (NCC) and is an important region to investigate the early Precambrian evolutionary history of the NCC. The Taishan association, consisting of a ~2.7 Ga komatiite–tholeiite sequence and a ~2.5 Ga felsic volcano‐sedimentary sequence, is the major lithological assemblage in the WSP. In the Qixingtai area, the felsic volcano‐sedimentary sequence, partly subjected to anatexis, is composed of hornblende gneiss, voluminous fine‐grained biotite gneiss and biotite plagioclase gneiss. SHRIMP zircon dating shows that the protolith of the biotite plagioclase gneiss formed after ca . 2.53 Ga. The tonalite intrusion into the volcanic protoliths of the fine‐grained biotite gneiss and biotite plagioclase gneiss occurred at 2.52 Ga. Our age data constrain the time of formation of the felsic volcano‐sedimentary sequence in the Taishan area as 2.53–2.52 Ga. The majority of zircons from the felsic volcano‐sedimentary rocks have intermediate ε Hf (t) values (−1.2 to +2.1). The whole rock Nd isotopes of the Taishan felsic volcano‐sedimentary rocks yield the ε Nd (t = 2522 Ma) values of +2.6 to −1.8 and TDM2 ages 3.03–2.68 Ga. These values indicate the pre‐existing crust was reworked at the end of the Neoarchaean (~2.5 Ga). The Taishan felsic volcano‐sedimentary rocks are rhyodacite–dacite and andesite in composition. These rocks and the tonalite display similar high SiO2 (65–72 wt.%) and low MgO (1–2 wt.%) content. In contrast, the minor andesites in the area have lower SiO2 (61–62 wt.%) and higher MgO (5.3–6.3 wt.%), suggesting more mantle contribution during their petrogenesis. However, the Mg‐rich andesites have identical rare earth element and multi‐element patterns with the rhyodacite–dacites and distinguish them from the Taishan sanukitoids. We suggest that the 2.53–2.52 Ga felsic volcanics of the Taishan association are the products of partial melting of a subducted oceanic crust. The andesites were produced by minor modification of the ascending tonalite–trondhjemite–granodiorite‐type magma by the mantle wedge. Our study indicates that (1) the tectonic regime of the WSP greenstone belt was dominated by an arc‐subduction system at ~2.52 Ga and (2) the 2.53–2.52 Ga felsic volcano‐sedimentary rocks and intrusive tonalite are the products of crustal reworking. The felsic volcano‐sedimentary sequence of the Taishan association and other ~2.5 Ga arc‐like assemblages in the NCC provide important clues to understand the nature of the tectonothermal events at the end of the Neoarchaean. Copyright © 2013 John Wiley & Sons, Ltd.